The land/ocean interactions in the coastal zone of west and central Africa - Barusseau, Jean-Paul; Descamps, Cyr; Diop, Salif (Estuaries of the World, 2014)
Although the main focus of this book is on the estuaries, its scope goes well beyond this particular coastal feature. Indeed, the estuary can only be considered as part of the life cycle of the entire river and the marine area it feeds into: an area particularly subject to human and natural pressures.   The main estuaries and deltas of West and Central Africa region provide a variety of goods and services to its coastal population. The most important of them are related to critical fish habitat, wood and charcoal from mangroves, as well as space for agriculture, aquaculture, urban development, tourism and transport.   Particular emphasis has been made in this book on mangroves that play a significant role in terms of flood control, groundwater replenishment, coastline stabilization and protection against storms. They also retain sediments and nutrients, purify water, and provide critical carbon storage. Such hydrological and ecological functions explain the focus on serving mangrove ecosystems and the nearby communities, which draw significant income from fishing, rice production, tourism, salt extraction and other activities such as harvesting honey and medicinal plants, hence the need for preserving mangrove ecosystems to ensure sustainability of the estuaries and deltas of West and Central Africa region.   The book has a foreword by Mr. Achim Steiner, United Nations Under-Secretary General and Executive Director of UNEP who is stating that credible and up-to-date information is essential for the public at large but more specifically for scientists, researchers, managers, decision-makers all working together in order to safeguard, protect and sustainably manage estuaries, deltas and lagoons, and the coastal and ocean waters of Western and Central Africa.